Analisis Pemikiran Jean Baudrillard tentang Simulasi dan Realitas dalam Konteks Era Digital - Ropip Asharudin (Gunung Djati Conference Series, 2023)
This article discusses Jean Baudrillard's thoughts on simulation and reality in the context of the digital era. This study used a qualitative approach with a descriptive-analytical method. Jean Baudrillard's thoughts in this study occupy a position as a formal object. While simulation and reality are the material objects. The digital era is the scope of discussion in this study. The results of the research and discussion show that Jean Baudrillard in his works has explained how technology and digital media strengthen the phenomenon of simulation and blur the boundaries between reality and imagination, here Baudrillard sees that the world has turned into a simulacrum, where representations and experiences created by the media the masses have replaced reality. In the end, this article reaches the conclusion that in the digital era, hyperreality is becoming increasingly important as a substitute for reality, the impact of the digital era on the concept of simulation and fake reality is experiencing ecstasy.